Crystal structure of ((5,5′-dimethoxy-2,2′-(1,2-phenylenebis(nitrilomethylidyne)))diphenolato-κ4O,N,O′,N′)copper(II), C22H18N2CuO4 - Ling Zhao; Xin Wang; Liguo Yang; Linna Gao (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C22H18N2CuO4, monoclinic, P21/n (no. 14), a = 15.7861(11) Å, b = 5.3211(4) Å, c = 21.6563(16) Å, β = 92.129(4)°, V = 1817.9(2) Å3, Z = 4, Rgt(F) = 0.0254, wRref(F2) = 0.0765, T = 298 K.